The meaning of Mariah Carey - Carey, Mariah (Andy Cohen Books, Henry Holt and Company, 2020)
The global icon, award-winning singer, songwriter, producer, actress, mother, daughter, sister, storyteller, and artist tells the unfiltered story of her life.